The Study Of The Self-Attitude Of Displaced People In The Conditions Of Adaptation To The New Social Environment - Sargsyan, Levon (Զանգակ հրատ.)
The work focuses on the characteristics of a person's self-attitude in the context of social-psychological displacement problems. This study examines how displacement can lead to changes in a person's characteristics and the specific socio-psychological challenges they face in their new living environment. The research focuses on understanding how self-attitude is expressed during socio-psychological adaptation among displaced individuals. The findings reveal that individuals who experience displacement in a new social environment tend to exhibit low self-confidence, self-management, self-evaluation, self-acceptance, and self-analysis. As a result, they often face internal conflicts and engage in self-criticism. This suggests that during the initial months of displacement, individuals develop a negative self-attitude, with positive aspects of self-attitude diminishing. However, the second stage indicates that positive changes in self-attitude are crucial for the survival and well-being of the individual and their family.
Keywords: Psychology; Social environment